PERFORMANCE AND ANTIMICROBIAL POTENTIALS OF ONION (Allium cepa Linn) BULB AND WALNUT (Tetracarpidium conophorum Mull. Arg) LEAF IN THE DIET OF Clarias gariepinus Burchell, 1822 (2014)
High cost of conventional feedstuffs and competition between livestock and fish for ingredients necessitate research into low cost, non-conventional feedstuffs for profitable fish farming. In aquaculture, the emphasis is on producing feeds that promote growth and health of fish. There is scanty documentation of the potential of onion (Allium cepa) bulbs and walnut (Tetracarpidium conophorum) leaves in fish production. The growth performance of Clarias gariepinus on diets containing Onion Bulb (OB) and Walnut Leaf (WL) and their antibacterial activities were therefore investigated. Growth experiments, replicated 3 times with 20 fish per replicate, were carried out for 18 weeks on C. gariepinus juveniles. Experimental diets composed of control (0%), OB2 (0.5%), OB3 (1.0%), OB4 (1.5%), OB5 (2.0%), WL6 (0.5%), WL7 (1.0%), WL8 (1.5%) and WL9 (2.0%) were fed twice daily at 3% body weight. Mean Weight Gain (MWG), Specific Growth Rate (SGR) and Feed Conversion Ratio (FCR) were measured. Also, Packed Cell Volume (PCV), Haemoglobin (Hb), Total Protein (TP), Amino Alanine Transferase (ALT) and Aspartate Amino Transferase (AST) contents were determined using standard methods. Antibacterial activities and inhibition of diameter of ethanol and methanol extracts of OB and WL were evaluated against four clinical strains of bacteria isolates from C. gariepinus and Oreochromis niloticus using agar well diffusion method. Microbial loads of water and fish tissues (skin, gill, intestine and liver) were determined using American Public Health Association (APHA) methods. Clarias gariepinus juveniles were innoculated with Pseudomonas aeruginosa at 5.0x10-6cfu/mL intraperitoneally and fed the different diets to assess their Level of Protection (LP). Wound (1cm2) was created on lateral and caudal parts of the C. gariepinus and percentage Dermal Wound Healing (DWH) was investigated using standard methods. Data were analysed using descriptive statistics and ANOVA at p=0.05 Fish on OB and WL based diets had higher growth rates than the control diet but C. gariepinus fed WL8 had significant higher MWG, SGR and FCR of 53.81±1.20g, 1.09±0.11g and 2.16±0.01 respectively. The PCV (34.5±0.7%), Hb (10.65±0.07g/dL), TP (5.70±0.99g/dL), ALT (22.50±3.40 μ/L) and AST (139.00±9.90 μ/L) in WL were significantly higher than those of OB. The OB and WL extracts had inhibition zones of 10±0.01mm and 12±0.01mm diameter respectively against P. aeruginosa; 11±0.00mm and 11±0.01mm diameter against Pseudomonas fluorescens; 11±0.01mm and 13.5±0.01mm diameter against Staphylococcus aureus. Microbial loads in water (log10cfu/mL) 4.37±0.02, skin, gill, intestine and liver (log10cfu/g) were 3.35±0.05, 3.20±0.06, 3.27±0.04 and 3.25±0.07 respectively in fish on WL diets. These values were significantly lower than the corresponding values for OB. The LP against P. aeruginosa were higher in WL8 (90%) and OB2 (90%) than uninnoculated fish. The DWH of C. gariepinus was better on lateral and caudal parts (100%, 100%) in WL8 compared to the control (98%, 80%) respectively. Fish fed with onion bulb and walnut leaf diets had improved mean weight gain, specific growth rate and feed conversion ratio, and were more resistant to Pseudomonas aeruginosa infection